Исследование АТР- и пирофосфатсвязывающих участков триптофанил- тРНК-синтетазы с помощью фосфонатных аналогов АТР и пирофосфата - Меркулова, Т.И.; Нурбеков, М.К.; Ковалева, Г.К. (Биополимеры и клетка, 1986)
АТР- и пирофосфатсвязывающие участки бычьей триптофанил-тРНК- синтетазы (КФ 6.1.1.2) исследовали с помощью фосфонатных аналогов АТР и неорганического пирофосфата – аденозил-5'-фосфорилдифосфоната (Аррср), аденозил-5'-дифосфонилфосфата (Арсрр) и метилендифосфоната (РсР). На основании полученных результатов высказано предположение, что обнаруженное ранее пирофосфорилирование фермента пирофосфатом, отщепляющимся от АТР при образовании аденилата, может быть одним из факторов, предотвращающих синтез Ар₄А на триптофанил-тРНК-синтетазе. АТР- і пірофосфатзв’язувальні ділянки бичачої триптофаніл-тРНК-синтетази (КФ 6.1.1.2) досліджували за допомогою фосфонатних аналогів АТР і неорганічного пірофосфату – аденозил-5'-фосфорилдифосфонату (Аррср), аденозил-5'-дифосфонілфосфату (Арсрр) і метилендифосфонату (РСР). На основі отриманих результатів висловлено припущення, що виявлене раніше пірофосфорилювання ферменту пірофосфатом, який відщеплюється від АТР при утворенні аденілату, може бути одним із факторів, що запобігають синтезу Ар₄А на триптофаніл-тРНК-синтетазі. ATP and pyrophosphate-binding sites of bovine tryptophanyl-tRNA-synthetase were studied by phosphonate analogs of ATP and inorganic pyrophosphate — adenosyl-5'-phospho-ryldiphosphonate (Appcp), adenosyl-5'-diphosphonylphosphate (Apcpp) and methylene-diphosphonate (PcP). Methylenediphosphonate can fulfil the role of PP; in the reaction of tryptophanyl adenylate pyrophosphorolysis with the formation of Appcp, the only product of the reaction. Phosphonate analogs of ATP inhibit the reaction of tryptophan-dependent ATP-[32P]PPi- exchange competitively with respect both to ATP (Ki~0.7 mM for Apcpp and ~3.6 mM for Appcp) and PP; (Ki~2.5 mM for both inhibitors). The two analogs interact with the isolated tryptophanyl adenylate-enzyme complex, corresponding phosphonate analogs of Ap4A being formed. On the basis of the results obtained an assumption is made that the observed earlier enzyme pyrophosphorylation by pyrophosphate, which is cleft from ATP in the course of adenylate formation, may be one of the factors preventing the synthesis of Ap₄A on tryptophanyl-tRNA synthetase.